Auto-exhaust pollution effects on the leaf structure of Olea europea L. (Bangladesh Journal of Botany, 2020)
Effects of auto-exhaust pollution on the leaf structure of Olea europea L. (Olive) were determined. Olive leaves were collected from three areas, such as, no low and heavy traffic areas with different traffic intensity. Anatomical layer thickness of leaves was studied in cross sections. Results showed that, the least values of layer thickness of leaves and total leaf thickness were obtained from high traffic area. Auto-exhaust pollution caused chlorosis and necrosis in morphological structure of olive leaves as well. The plant tolerated traffic-based pollution stress by decreasing anatomical layer thickness, however chlorosis occurred. Therefore, olive leaves can be used as a bio-indicator for traffic-based pollution because of their higher sensitivity to exhausts gases.